Exotic μτjj events from heavy ISS neutrinos at the LHC - Arganda Carreras, Ernesto (2016)
In this letter we study new relevant phenomenological consequences of the right-handed heavy neutrinos with masses at the O(1)TeV energy scale, working within the context of the Inverse Seesaw Model that includes three pairs of quasi-degenerate pseudo-Dirac heavy neutrinos. We propose a new exotic signal of these heavy neutrinos at the CERN Large Hadron Collider containing a muon, a tau lepton, and two jets in the final state, which is based on the interesting fact that this model can incorporate large Lepton Flavor Violation for specific choices of the relevant parameters, particularly, the neutrino Yukawa couplings. We will show here that an observable number of μτ. jj exotic events, without missing energy, can be produced at this ongoing run of the LHC.